Antibiotik Cefadroksil pada Pasien Infeksi Saluran Pernapasan Atas (ISPA) - Fhahri Mubarak; Rahmad Aksa; Afrilia Nursal (Jurnal Ilmiah Kesehatan (JIKA), 2021)
Upper Tract Infection is an infection that occurs in the nasal cavity, sinuses, and throat. Some of the diseases included in this infection are colds sinusitis, tonsillitis and laryngitis. This study is to determine the profile of the use of cefadroxil drugs in ARI patients in several places. ARI (Acute Respiratory Infection) affects all ages, but babies and toddlers are the most susceptible to infection. This study used secondary data got from literature searches on the use of cefadroxil antibiotics in patients with ARI. Data taken as data on the percentage of the number of patients based on the type of age, type of work, type of education. The patient’s domicile based on the ward in several places. The results showed that from several journals, among them were male patients who were most affected by Acute Respiratory Infection (ARI). This was due to frequent activities outside the home. In general, the profile of the use of cefadroxil antibiotics in patients with acute respiratory infections (ARI) is in accordance with the guidelines from the WHO and the Ministry of Health 2005.